Evaluation of Power Maximization and Curtailment Control Methods for Converters in Wearable Photovoltaic Energy Harvesting Applications - F. Selin Bagci; Katherine A. Kim; Yu-Chen Liu; Yi-Hua Liu (IEEE Open Journal of Power Electronics, 2022)
As wearables become more widely adopted, powering them from ambient energy sources can improve reliability and reduce reliance on batteries. Solar photovoltaic (PV) power is a viable power source for such emerging applications. However, because wearable applications bend and move with the user's motion, the PV panels used in these applications experience varying light intensities over multiple PV cells that reduce power generation in traditional series-string configurations. To address the PV power reduction problem, a configuration of boost converters with parallel-connected outputs are utilized, which is effective in uneven lighting conditions. Depending on the load demand and available solar power, a converter control system should quickly transition between maximum power point tracking (MPPT) and power curtailment operation. This work evaluates MPPT (perturb & observe and constant-voltage) algorithms and power curtailment (over-voltage shut-off and flexible power point tracking) methods on their effectiveness in wearable applications. Experimental results verify that the perturb & observe with flexible power point tracking effectively adapts to changes in the load and light conditions while maintaining 30% and 31% higher output power, respectively. It also maintains the maximum component temperature below 29 $^{° }$ C which is a safe temperature for wearable applications.